PENGARUH TINGKAT PENDIDIKAN SEKOLAH TERHADAP MOTIVASI BEKERJA PADA SEKTOR PERTANIAN DI DESA KARANGNANAS, KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Hari Walujo Sedjati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2008)
The education degree was found related to motivation worked at the other peasant in village, because the peasant generally don’t react to new ideas with a positive attitude. To say that peasants are tradition oriented is to state a truism. The peasants to follow those ways be known will produce positive, even though small scale, results rather than to try a new idea that might end in failure and thereby endanger his existence. The lack of peasant innovativeness is a funtion of scarce economic resources or of technology inappropriate for village settings. Peasants are poor, and a lack of ready capital undoubteddly serves to discourage the adoption of those new ideas which require cash outlay. Peasants are poor in technological resources and human resources. Peasants a relatively low capital income and comparatively low productivity per person, little commerce and high self sufficiency, a high rate of illiteracy, limited mass media facilities, inadequate nutrition and high death rates and shorts life expactancy, So that the education degree was found to be related other became peasant. Product Moment score are negatively related : - 0,289. This research in Karangnanas village, Sokaraja subdistrict. Banyumas regency, Jawa Tengah Province. Key words : Peasant. Education. Motivation.